Cytotoxic activities, apoptotic induction and mitochondrial studies of selected cationic schiff bases from the thiosemicarbazone family / Saravana Kumar Sinniah - Saravana Kumar , Sinniah (2016)
Thiosemicarbazone (TSC) is a Schiff base that has been receiving considerable attention owing to its promising biological implication and remarkable pharmacological properties such as anti-tumor, anti-viral, anti-microbial and anti-parasitic. Currently, the most promising drug candidate of this class would be Triapine (3-aminopyridine-2-carboxaldehyde thiosemicarbazone) which has entered phase II clinical trials as a potent anti-cancer chemotherapeutic agent. In the present study, Schiff base ligands from (3-formyl-4-hydroxy-phenyl)methyl-triphenyl-phosphonium (T) and varied substituents at N4 atom namely thiosemicarbazide itself [(tsc)T], 4-phenylthiosemicarbazide [P(tsc)T], 4,4-fluorophenylthiosemicarbazide [FP(tsc)T], 4-ethylthiosemicarbazide [E(tsc)T], 4,4-ethylphenylthiosemicarbazide [EP(tsc)T], 4-methylthiosemicarbazide [M(tsc)T] and 4,4-dimethyl thiosemicarbazide [DM(tsc)T] were synthesized by condensation reactions. These compounds have been characterised by IR, NMR, HRMS and X-ray crystallography and were in confirmation with the proposed structures. Growth inhibitory effect of the compounds were performed against six human cell lines, namely PC-3 (prostate adenocarcinoma), A549 (non-small cell lung cancer), MCF7 (breast carcinoma), MDA-MB-231 (breast adenocarcinoma), HCT 116 (colorectal carcinoma) and RWPE-1 (prostate normal). MTT assay indicated that [P(tsc)T], [FP(tsc)T], [EP(tsc)T] and [DM(tsc)T] exhibit significant inhibitory effect on PC-3 cells with least damage to RWPE-1 cells. These four cytotoxic compounds induce prominent morphological changes such as rounding, shrinkage, membrane blebbing and the loss of cell to cell contacts compared to untreated cells which were affirmed by AO/EB assay. The untreated cells were stained uniformly green; meanwhile most of the cells treated with 50 μM or higher concentration for 48 and 72 hours were stained bright orange to red, indicating late apoptosis and/or necrosis phase. These results were further supported by Annexin V/PI assay which clearly indicated that the compounds induce apoptosis in PC-3 cells. The untreated cells showed approximately 90 % cell viability meanwhile cells treated with 100 μM of the compounds for 72 hours showed approximately 50 % drop in cell viability, indicating that these compounds demonstrate cytotoxic properties in dose- and time-dependent manner. Furthermore, the cell cycle assay results showed that the cell cycle was arrested in G0/G1 phase when treated with the compounds for 72 hours. Mitochondrial membrane potential assay result also implied that the apoptosis could be due to mitochondria mediated pathway by showing a steady drop in polarized cells with increasing dose for treatment duration of 24 hours. In conclusion, the results obtained showed that the newly synthesized compounds induce significant cytotoxic properties by inhibiting highly metastasis prostate cancer cell line growth. Taken together, these data suggest that the newly synthesized TSC compounds warrant further systematic investigation as anti-cancer agent, and they can serve as building blocks for further modifications